Current topics in human varicella infection: Pearls and challenges - Luthvia Annisa; Mohamad S. Hakim; Abu T. Aman (Published by Universitas Gadjah Mada, 2024)
Varicella zoster virus (VZV), an alphaherpesvirus, is a highly contagious and neurotropic virus infecting the majority of the adult and pediatric population worldwide. Varicella zoster virus is the only human herpesvirus for which a licensed live attenuated vaccine has been developed. It can be considered that additional study on VZV is superfluous given the significant success of the VZV vaccines. This has been the case for other viruses including rubella and measles, for which effective vaccinations are widely available. Contrarily, much regarding VZV, a complex and chronic human disease due to its latency, still needs to be uncovered. Over the past two decades, our understanding of the molecular biology of VZV and its pathogenicity has expanded. In this review, we discussed our recent understanding of VZV biology, pathogenesis as well as its clinical aspect, including diagnosis, clinical management, and vaccine development.